Diseño, construcción y arranque de operación de un reactor de lodos activados a escala de laboratorio - Crespo Ruiz, Michelle Stefania (2018)
The present work of investigation evaluated the efficiency of the elimination of the physical-chemical parameters of an activated sludge reactor in which the domestic residual water coming from the Shanshayacu creek in Quitumbe in the south zone of the DMQ was treated. For the development of the project, it was essential to know the quality of the wastewater to be treated; the design, construction and operation in the laboratory of the Environmental Engineering Career of the Salesiana Polytechnic University of the complete mixing and continuous flow reactor was carried out which was determined after an analysis, as the best option of the treatment system according to the characteristics of the water. The reactor operated for a period of 56 days; the activated sludge that was used for the process was mature sludge that was obtained from the wastewater treatment plant of the parish of Nono, it was stabilized for a period of 20 days, there was a daily control of certain parameters such as concentration of dissolved oxygen in the mixture liquor with an average value of 5.21 mg / L, the temperature with an average standard variation of 16.39 ° C and the pH whose values were close to neutral. The removal efficiency of the treatment system started with 36.78% of COD and 28% of BOD and ended with 96.08% of COD and 88% of BOD, which determined that the process exceeded the theoretical efficiency by 13, 75%.